Interphase Chromosomes in Replicative Senescence: Chromosome Positioning as a Senescence Biomarker and the Lack of Nuclear Motor-Driven Chromosome Repositioning in Senescent Cells - Mehta, Ishita S.; Riyahi, Kumars; Pereira, Rita Torres; Meaburn, Karen J.; Figgitt, Martin; Kill, Ian R.; Eskiw, Christopher H.; Bridger, Joanna M. (Frontiers in Cell and Developmental Biology, 2021)
This study demonstrates, and confirms, that chromosome territory positioning is altered in primary senescent human dermal fibroblasts (HDFs), when compared to young proliferating HDFs. The chromosome territory positioning pattern is very similar to that found in HDFs made quiescent either by serum starvation or confluence; but not completely. A few chromosomes are found in different locations. One chromosome in particular stands out, chromosome 10, which is located in an intermediate location in young proliferating HDFs, but is found at the nuclear periphery in quiescent cells and in an opposing location of the nuclear interior in senescent HDFs. We have previously demonstrated that individual chromosome territories can be actively and rapidly relocated with 15 minutes after removal of serum from the culture media. We now also demonstrate rapid chromosome movement in HDFs after heat-shock at 42oC. These chromosome relocations require nuclear motor activity through nuclear myosin 1beta. However, this current study reveals that in senescent HDFs chromosomes can no longer be relocated to expected nuclear locations upon these two types of stimuli. This coincides with a completely different organisation and distribution of NM1 within senescent HDFs.